Empirical Constructing of the Managerial Talent Category in Education - Justyna Śmietańska (Nicolaus Copernicus University in Toruń, 2020)
The article addresses the issue of modern management of educational institutions. The subject of empirical research was the category of managerial talent in education. Effort is made to present the indicated subject matter in a multidimensional and holistic manner, combining the category and advantages of quantitative research methodology, psychometric measurement, and qualitative research methods. The study group consisted of teachers and head teachers at Polish state schools (primary schools, junior high schools, upper-secondary schools). The head teachers were given in-depth individual interviews (IDIs) and psychological tests, and teachers responded to an Internet survey (CAWI). The main objective of the empirical research was to construct a category described as managerial talent in education. On the basis of the research, the characteristic components of this category were distinguished. Special emphasis was also placed on the pragmatic dimension of the studied phenomenon, the results obtained and conclusions drawn - for this reason the paper includes numerous reflections and practical implications concerning everyday educational life and modern education management